2008
DOI: 10.1128/jb.00585-08
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Inactivation of the Mycobacterial Integral Membrane Stearoyl Coenzyme A Desaturase DesA3 by a C-Terminus-Specific Degradation Process

Abstract: DesA3 (Rv3229c) from Mycobacterium tuberculosis is a membrane-bound stearoyl coenzyme A ⌬ 9 desaturase that reacts with the oxidoreductase Rv3230c to produce oleic acid. This work provides evidence for a mechanism used by mycobacteria to regulate this essential enzyme activity. DesA3 expressed as a fusion with either a C-terminal His 6 or c-myc tag had consistently higher activity and stability than native DesA3 having the native C-terminal sequence of LAA, which apparently serves as a binding determinant for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
(68 reference statements)
2
10
0
Order By: Relevance
“…The TbD1 region was absent from the Zaragoza strain, and the mgtC 182 (Arg-His), ogt 44 (Thr-Ser), and ung 501 (Leu-Leu) SNPs characteristic of the Haarlem genotype were not present, which allowed us to classify Zaragoza as a non-Haarlem but "modern" strain of M. tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The TbD1 region was absent from the Zaragoza strain, and the mgtC 182 (Arg-His), ogt 44 (Thr-Ser), and ung 501 (Leu-Leu) SNPs characteristic of the Haarlem genotype were not present, which allowed us to classify Zaragoza as a non-Haarlem but "modern" strain of M. tuberculosis.…”
Section: Resultsmentioning
confidence: 99%
“…Its product is a stearoyl-coenzyme A desaturase (DesA3) implicated in the synthesis of oleic acid and considered to be essential for intracellular growth in macrophages (44,45). In addition, DesA3 is a target of the secondline antituberculosis drug isoxyl, which was used together with isoniazid in multiple-drug therapy in the 1960s (43,44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies in murine microsomes [11] and differentiated mouse 3L3-L1 adipocytes [15] showed post-translational proteolytic processing of the N-terminus of the enzyme, subsequent inactivation, and proteosome-directed degradation. Interestingly, DesA3, part of the stearoyl-CoA desaturase complex from Mycobacterium tuberculosis [16, 17], is also targeted for rapid proteolytic degradation, but in this case by a prokaryotic degradation complex with specificity for the C-terminus [18]. The multiple layers of regulation of desaturase activity, in diverse organisms, emphasize the importance of this enzyme in cellular function [7], but also complicate recombinant expression using living hosts.…”
mentioning
confidence: 99%